How Film Mulch Increases the Corn Yield by Improving the Soil Moisture and Temperature in the Early Growing Period in a Cool, Semi-Arid Area - Meng Kong; Yu Jia; Yan-Jie Gu; Cheng-Long Han; Xin Song; Xiao-Yan Shi; Kadambot H.M. Siddique; Pandi Zdruli; Feng Zhang; Feng-Min Li (Agronomy, 2020)
Film mulch increases the crop grain yield via topsoil moisture and temperature improvement in cool, semi-arid areas, but little is known about the role of the hydrological and thermic relationship between early and later crop growth seasons in the improving grain yield. We conducted a field experiment to compare polyethylene film mulching (PM) with no mulching (CK) in 2014 and 2015 on the semi-arid Loess Plateau of China. Compared to CK, PM decreased evapotranspiration before the twelve-leaf stage (V12), but increased evapotranspiration after the V12 stage, and significantly increased the topsoil temperature before the six-leaf stage (V6) and the accumulation of soil growing degree days. Corn plants with PM treatment reached the V6 stage earlier, significantly enhancing the contemporary dry matter accumulation. The harvest index, 100-grain weight, and grain yield significantly increased in PM relative to CK in both years. The growing period to the whole growing season evapotranspiration ratio had a negative correlation with the grain yield before the V12 stage, but a positive correlation after the V12 stage. The grain yield had a negative correlation with the air growing degree days (GDDair) before the V6 stage, but positive correlation from silking to harvest. Conclusively, film mulch promoted the early development of maize via an increased soil temperature before the V6 stage, saved soil water before the V12 stage, resulted in a longer grain-filling period, and increased the GDDair and evapotranspiration during the grain-filling period, which is key to increasing the maize yield.